Tension between Human and Nature in sculpture - Imperial, Ricardo (CAP - Cadernos de Arte Pública / Public Art Journal, 2023)
This article explores the intricate relationship between sculpture and tension within the context of the human-nature dynamic. Through an examination of sculptural works such as “{Terra, Eu}”, “{Mão, vida}” and “The First Gesture,” we uncover the profound role tension plays in infusing artworks with dynamic energy, transforming passive viewers into active participants. Our exploration extends the horizons of sculptural practice by incorporating techniques like 3D modelling mixed with metalworking, and stone carving. Our research attempts to show a possible revaluation of conventional notions of reality and representation in response to the ever-evolving dynamics of our present. While acknowledging the limitations faced, including time constraints and the vastness of sculptural possibilities, we underscore the uncharted territories of emotional interactions within art and the exploration of art in virtual realms. In conclusion, this research serves as a point of departure for the ongoing investigation of the intersection between art and science, with a focus on deepening our understanding of our place within the natural order and the pursuit of balance and harmony in our interactions with the environment and sculpture.